Halal Certification for NU Muslim in Boyolali Regency : A Study on Purchasing Decision of Alwahida Neutralizer Herbal Product, Indonesia - Fathan Budiman; M Misbahul Mujib (Lakpesdam PCNU Kota Salatiga, 2020)
This study used an explanatory research type with a quantitative approach. The sample used in this research was 96 respondents who were NU Muslim consumers of HPAI products in Boyolali regency by using purposive sampling. Data collection methods used in this study were the halal certification questionnaire that included dimensions of sharia, ideology, science, experience, and practice. Technique of data analysis used in this research was descriptive analysis and simple linear regression analysis. The results of the study showed that halal certification did not have a significant influence on purchasing decisions. It was proven by the value of the halal certification count of 1,715 < t table 2.2791 and the significance of 0,90>0.05.